The child health implications of privatizing Africa’s urban water supply - Kosec, Katrina (International Food Policy Research Institute, 2013)
Can private-sector participation (PSP) in the urban piped water sector improve child health? The author uses child-level data from 39 African countries during 1986–2010 to show that introducing PSP decreases diarrhea among urban dwelling children under five years of age by 5.6 percentage points, or 35 percent of its mean prevalence.